GE_GERICHTE C/10833/2013 vom 16. Januar 2015 - GE Cour de justice (2015)
BAIL À LOYER; DÉFAUT DE LA CHOSE; DOMMAGES-INTÉRÊTS; PREUVE; HUISSIER; DROIT D'ÊTRE ENTENDU; MOTIVATION DE LA DÉCISION | CO.256.1; CO.259a; CO.259e; CO.42.1; Cst.29.2